Understanding the models of Indian fruit and vegetable supply chains - a case study approach. (16th December 2019) - Arshinder, K.; Balaji, M.
This study explores different perishable fresh fruit and vegetable (F&V) supply chain models and seeks to understand the issues and challenges that exist within the supply chains. A case study approach using qualitative methods was used to analyse the perishable F&V supply chains in a typical Indian metropolitan city. This study found that supply chain agents set their margins arbitrarily resulting in double marginalisation at each interface of the supply chains. Thus, double marginalisation and inefficiency in the domestic F&V supply chains results in massive wastage. F&V supply chains are impacted unequally and include food perishability, food quality and food safety based on the responsiveness of the supply chains. Insights found in this study will be useful, not only for F&V supply chain stakeholders, but also for policymakers to develop more efficient and responsive supply chain model in India and elsewhere with similar economic settings.